Redesign of Patient Wheelchair Type SM-8018 Based on Ergo-Total Function Deployment (ETFD) Integration - Heri Setiawan; Muhammad Yusuf; Micheline Rinamuti; Dominikus Budiarto; Yohanes Dicka Pratama; Achmad Alfian (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
Manual wheelchairs remain widely used in Indonesian health-care facilities, yet their design often does not fully accommodate local anthropometric characteristics and work patterns. The SM-8018 patient wheelchair used at PT SPU is operated by caregivers, exposing both patients and caregivers to potential ergonomic risks. This study aims to evaluate and redesign the SM-8018 wheelchair using an integrated Ergo-Total Function Deployment (ETFD) and House of Ergonomics (HoE) approach within a Total Ergonomics framework. A pre–post experimental design was applied involving 32 adult users and caregivers with at least six months of experience using or pushing the SM-8018. Data collection included anthropometric measurements, musculoskeletal complaints using the Nordic Body Map (NBM), subjective fatigue using the Japan Association of Industrial Health (JAIH) questionnaire, boredom scores, satisfaction using the Minnesota Satisfaction Questionnaire (MSQ) and voice of customers (VoC). VoC and ergonomic findings were mapped into a HoE matrix to derive priority design specifications through ETFD. Results showed notable mismatches between user anthropometry and key wheelchair dimensions, particularly seat depth and width, backrest and headrest height and angle, and push-handle height, which were associated with high levels of discomfort in the lower back, buttocks, shoulders and upper arms and with considerable fatigue. The ETFD–HoE analysis identified four primary redesign priorities: adjustment of push-handle height, optimisation of backrest and headrest geometry, refinement of seat dimensions and improvement of front-wheel stability. Pre–post comparisons indicated that musculoskeletal complaints and fatigue remained relatively high and in some cases increased, whereas boredom and satisfaction tended to change in a more favourable direction. These findings suggest that the first iteration of the SM-8018 redesign, although guided by Total Ergonomics principles, requires further refinement and system-level support. Nonetheless, the study demonstrates the feasibility of integrating ETFD, HoE and Total Ergonomics to systematically guide the improvement of low-cost hospital wheelchairs in the Indonesian context.